Population‐based validation of the recursive partitioning analysis–based staging system for oropharyngeal cancer. Issue 10 (15th April 2016) - Keane, Florence K.; Chen, Yu‐Hui; Tishler, Roy B.; Schoenfeld, Jonathan D.; Haddad, Robert I.; Goguen, Laura A.; Catalano, Paul; Neville, Bridget A.; Margalit, Danielle N.
Abstract: Background: The American Joint Committee on Cancer (AJCC) staging system does not adequately distinguish prognostic groups in the era of human papillomavirus (HPV)‐related oropharyngeal cancer. The purpose of this study was to validate a recursive partitioning analysis (RPA)‐based stage grouping on a population‐wide level. Methods: We identified 8427 patients in Surveillance, Epidemiology, and End Results (SEER) with nonmetastatic oropharyngeal cancer with unknown HPV‐status diagnosed from 2004 to 2008. We estimated the overall survival (OS) and head and neck cancer‐specific mortality by RPA stage and AJCC stage and compared the predictive power of the systems. Results: RPA stage was significantly associated with OS and head and neck cancer‐specific mortality ( p < .0001) with 5‐year OS of 70% for RPA‐I, 55.6% for RPA‐II, and 44.3% for RPA‐III. AJCC stage failed to divide patients into distinct subgroups. RPA stage had significantly improved predictive ability versus AJCC stage for OS (c‐statistic: 0.60 = RPA vs 0.54 = AJCC) and head and neck cancer‐specific mortality (c‐statistic: 0.62 = RPA vs 0.55 = AJCC). Conclusion: The RPA‐based stage grouping divided patients into prognostically distinct cohorts and provided superior prediction of OS and head and neck cancer‐specific mortality compared to AJCC staging. © 2016 Wiley Periodicals, Inc. Head Neck 38: First–1538, 2016